New quinoline-based triazole hybrid analogs as effective inhibitors of α-amylase and α-glucosidase: Preparation, in vitro evaluation, and molecular docking along with in silico studies - Khan, Yousaf; Iqbal, Shahid; Shah, Mazloom; Maalik, Aneela; Hussain, Rafaqat; Khan, Shoaib; Khan, Imran; Pashameah, Rami Adel; Alzahrani, Eman; Farouk, Abd-ElAziem; Alahmdi, Mohammed Issa; Abd-Rabboh, Hisham S. M. (Frontiers in Chemistry, 2022)
The 7-quinolinyl bearing triazole analogues were synthesized (1-19) and according to literature known protocol were screened in vitro for their α-amylase and α-glucosidase inhibitory profile. All analogues showed moderate to good inhibitory potentials ranging between 0.80 ± 0.05µM to 40.20 ± 0.70 µM and 1.20 ± 0.10 µM to 43.30 ± 0.80µM against α-amylase and α-glucosidase. Among the series, analogues 4 (IC50 = 0.80 ± 0.05 µM), (IC50 = 1.20 ± 0.10 µM) and 5 (IC50 = 1.50 ±0.10µM), (IC50 = 1.90 ± 0.10µM) with flouro substitution at phenyl ring of the triazole ring were identified to be the most potent inhibitors against α-amylase and α-glucosidase enzymes. The structure of all the newly synthetics analogues were confirmed by using different types of spectroscopic techniques such as HREI-MS, 1H- and 13C- NMR spectroscopy. To find structure-activity relationship, molecular docking studies were carry out to understand the binding mode of active inhibitors with active site of enzymes and results supported the experimental data.